Avaliação de uma fração polissacaridica da alga Lobophora variegata (Lamouroux) em modelo de artrite induzida em ratos por Zymosan - Paiva, Almino Afonso de Oliveira (2010)
Fucans seaweed Lobophora variegata estructures are known for their chemical and biological properties. In this study, we analyzed, the action of fucans L. variegata and the fractions purified with acetone in Zymosan-induced arthritis. After differential fractionation with acetone, six fractions were obtained and named F0.3, F0.5, F0.8, F1, F1.5 and F2. The results showed that the fraction F1 showed high yield (51.9%) and was chosen for studies of antioxidant activity and induced arthritis. Nuclear magnetic resonance (NMR) of 13C showed signals at 103.3 and 15.78 ppm that are assigned to links β13 galactose and of the C6 methyl fucose, respectively. The infrared (IR) showed absorbance at 1238 and 850 cm-1 which are attributed to sulfate. The fraction F1 showed antioxidant activities in vitro. For analysis of inflammatory parameters chosen the polysaccharide was administered in different doses (25, 50 and 75 mg / kg ip, per body weight) and diclofenac sodium (5 mg / kg ip) and L-NAME (25 mg / kg ip) in groups of animals (n = 6). After 6 h, were analyzed for cellular influx and levels of nitrite. In experiment five days, were made analysis of swelling and serum TNF-α. Histopathological analysis were performed for confirmation of results. The fraction F1 (25, 50 and 75 mg / kg ip) reduced the cellular influx (52.1 to 96.7%) and nitric oxide levels (27.2 - 39%) compared to control group. The reduction of edema (63.4 - 100%) and serum TNF-α (p <0.001) were observed when the polysaccharide F1 administered at a dose (50 mg / kg) These results suggest that these heterofucanas of Lobophora variegata have besides the activity antioxidant and potential anti-inflammatory activity in arthritis induced by zymosan